Stability Analysis of a Nonlinear System with Different Growth Functions - Kamrujjaman, Md; Niger, Ashrafi Meher (GANIT: Journal of Bangladesh Mathematical Society, 2018)
A competitive mathematical model for the growth of two species is considered in this study. The main goal of the present study is to investigate the roles of two different growth functions: the logistic growth and the food limited growth. We established the main results that determine the asymptotic stability of semi-trivial as well as the coexistence solutions. If higher carrying capacity is embodied for the population following logistic growth then competitive exclusion of a food limited population is imminent and vice versa. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 111-119